A Technique of teaching vectors - Angeles, Celia Z. 1941- (s.n.], 1967)
This study describes a technique in teaching vectors in high school with the aid of the "parallelogram of forces" apparatus and a flannel board. The representation of the basic concepts in vector operations is developmental, with students gaining skills as the lesson proceeds from the very simple to the more complex.